PENYULUHAN TENTANG KUALITAS LAYANAN PRIMER DI KLINIK PRATAMA TANJUNG DELI SERDANG - Elisabeth Dame Manalu; Rostiodertina Girsang; Evi Hasnita (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
Pratama clinic is a clinic that provides basic medical services served by general practitioners and led by a general practitioner. Based on the license, this clinic can be owned by a business entity or an individual. In the service system in the era of the National Health Insurance (JKN) organized by the Social Security Administering Body (BPJS) in the health sector, pratama clinics were placed as primary services on par with puskesmas. As a primary service, a pratama clinic is required to meet certain requirements as quality assurance or the quality of services provided for BPJS participants to obtain treatment or referral services related to the health problems they are experiencing. As service providers, officers need good knowledge and understanding regarding service quality at the Klinik Pratama Tanjung Deli Serdang, so that with good knowledge and understanding the officers can provide services that meet the standards set and satisfy visiting patients.